Systemic lupus erythematosus and thymus persistens – A case report - Stević-Carević, Silvija S.; Glišić, Branislava; Dedović, Jelena (Vojnosanitetski pregled, 2017)
Introduction. Thymus plays an important role in the maturation of T-lymphocytes and in the development of immune tolerance. Its involution comes after puberty. If thymic tissue remains preserved in an advanced age it is considered to be the thymus persistens. According to the available data, 5% of patients with a thymoma have some of the autoimmune disorders. Medical data on the systemic lupus erythematosus (SLE) association with the thymus persistens are scarce. Case report. A 29-year-old patient was diagnosed with SLE at the age of 12. She was treated with continuous doses of corticosteroids and an antimalarial drug (chloroquine). After ten years, the first, and then two more recurrences of the disease with the last recurrence in 2011 occurred. The performed laboratory analyses indicated the disease activity. The radiography of thorax showed a change on the right lung, with enlarged mediastinal shadow. Therefore the multislice computed tomography (MSCT) of thorax was made. The pathohistology findings confirmed that the change on the right lung was focus of chronic pneumonitis, while the change in mediastinum was thymus persistens. The thymectomy was performed. Due to pneumonitis, the treatment of SLE was continued with corticosteroids, antimalarial drug and pulse doses of cyclophosphamide. The patient received six monthly and six quarterly pulsed doses of the drug. The remission of the disease maintained all the time. Conclusion. The disorder of thymic function should be considered as a possible cause in the development of SLE. Though the effect of thymectomy is difficult to assess, patients should be carefully monitored.